Effects of Fruit and Vegetable Low Molecular Mass Fractions on Gene Expression in Gingival Cells Challenged with Prevotella intermedia and Actinomyces naeslundii. (18th September 2011) - Canesi, Laura; Borghi, Cristina; Stauder, Monica; Lingström, Peter; Papetti, Adele; Pratten, Jonathan; Signoretto, Caterina; Spratt, David A.; Wilson, Mike; Zaura, Egija; Pruzzo, Carla
Abstract : Low molecular mass (LMM) fractions obtained from extracts of raspberry, red chicory, and Shiitake mushrooms have been shown to be an useful source of specific antibacterial, antiadhesion/coaggregation, and antibiofilm agent(s) that might be used for protection towards caries and gingivitis. In this paper, the effects of such LMM fractions on human gingival KB cells exposed to the periodontal pathogens Prevotella intermedia and Actinomyces naeslundii were evaluated. Expression of cytokeratin 18 (CK18) and β 4 integrin ( β 4INT) genes, that are involved in cell proliferation/differentiation and adhesion, and of the antimicrobial peptide β 2 defensin (H β D2) in KB cells was increased upon exposure to either live or heat-killed bacteria. All LMM fractions tested prevented or reduced the induction of gene expression by P. intermedia and A. naeslundii depending on the experimental conditions. Overall, the results suggested that LMM fractions could modulate the effects of bacteria associated with periodontal disease in gingival cells.